2006
DOI: 10.1007/s10832-006-9333-2
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of ZnGa2O4 phosphors synthesized by solution combustion method

Abstract: ZnGa 2 O 4 phosphors were synthesized by both SCM (solution combustion method) and SSRM (solid state reaction method). The characteristics of the both ZnGa 2 O 4 phosphors were investigated by TGA (Thermogravimetric analysis), SEM (scanning electron microscope), BET (Brunauer Emmett Teller), PL (photoluminescence) and XRD (X-ray diffraction). The particle size of SCM phosphor was about one-hundredth of SSRM phosphor. The PL intensity of SCM phosphor was about 1.5 fold higher than that of SSRM phosphor. The SCM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
(1 reference statement)
0
6
0
Order By: Relevance
“…The emission spectra of bulk ZnGa 2 O 4 show a blue emission band around 470 nm in the range of 300 and 600 nm. It originates from the self-activation center of the octahedral GaO 6 group in the spinel lattices and the Ga 3+ ions combine with UV-generated free electrons produced in oxygen vacancies. It has also been reported that the emission of ZnGa 2 O 4 is influenced by factors such as particle size, shape and crystallinity. In the case of our ZnGa 2 O 4 nanoparticles, obtained after furnace heating at 475 °C for 4 h on exciting at 356 nm, the emission spectra (Figure ) show a broad emission band in the range of 400 and 600 nm and a maximum emission peak at 469 nm with a shoulder at 437 nm. Similar results have been recently reported for ZnGa 2 O 4 nanocrystals prepared by combining thermolysis of single molecular precursor with the sol−gel method in the presence of a capping agent .…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The emission spectra of bulk ZnGa 2 O 4 show a blue emission band around 470 nm in the range of 300 and 600 nm. It originates from the self-activation center of the octahedral GaO 6 group in the spinel lattices and the Ga 3+ ions combine with UV-generated free electrons produced in oxygen vacancies. It has also been reported that the emission of ZnGa 2 O 4 is influenced by factors such as particle size, shape and crystallinity. In the case of our ZnGa 2 O 4 nanoparticles, obtained after furnace heating at 475 °C for 4 h on exciting at 356 nm, the emission spectra (Figure ) show a broad emission band in the range of 400 and 600 nm and a maximum emission peak at 469 nm with a shoulder at 437 nm. Similar results have been recently reported for ZnGa 2 O 4 nanocrystals prepared by combining thermolysis of single molecular precursor with the sol−gel method in the presence of a capping agent .…”
Section: Resultsmentioning
confidence: 79%
“…It originates from the self-activation center of the octahedral GaO 6 group in the spinel lattices and the Ga 3+ ions combine with UV-generated free electrons produced in oxygen vacancies. [33][34][35][36][37][38][39][40][41][42] It has also been reported that the emission of ZnGa 2 O 4 is influenced by factors such as particle size, shape and crystallinity. [33][34][35][36] In the case of our ZnGa 2 O 4 nanoparticles, obtained after furnace heating at 475 °C for 4 h on exciting at 356 nm, the emission spectra (Figure 5) show a broad emission band in the range of 400 and 600 nm and a maximum emission peak at 469 nm with a shoulder at 437 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Interstitial zinc defects produce the emission observed at 460 nm . Nanosized ZnCr 2 O 4 , ZnFe 2 O 4 , and ZnGa 2 O 4 also exhibited similar luminescence characteristics. The presence of Ga in ZnGa 2 O 4 is responsible for the origin of the luminescence properties, but in the case of ZnCr 2 O 4 , ZnFe 2 O 4 , and the present material, the luminescence behavior is due to the presence of Zn.…”
Section: Results and Discussionmentioning
confidence: 63%
“…ZnGa 2 O 4 phosphor has recently been studied as a potential candidate for field emission displays and plasma display panels. [31][32][33][34][35] In particular, as photocatalysts, ZnGa 2 O 4 nanoparticles have been found to present hydrolytic hydrogen generation activity, and their synthesis has been attempted by various methods, such precipitation and solution combination methods. 36,37) Therefore, the fabrication of nanomaterials containing ZnGa 2 O 4 and control of their dimensions will be of interest.…”
Section: Introductionmentioning
confidence: 99%